A pan-cancer analysis of the expression and molecular mechanism of DHX9 in human cancers - Wang, Yanfeng; Guo, Yongxin; Song, Yanping; Zou, Wenbo; Zhang, Junjie; Yi, Qiong; Xiao, Yujie; Peng, Jing; Li, Yingqi; Yao, Lei (Frontiers in Pharmacology, 2023)
Finding new targets is necessary for understanding tumorigenesis and developing cancer therapeutics. DExH-box helicase 9 (DHX9) plays a central role in many cellular processes but its expression pattern and prognostic value in most types of cancer remain unclear. In this study, we extracted pan-cancer data from TCGA and GEO databases to explore the prognostic and immunological role of DHX9. The expression levels of DHX9 were then verified in tumor specimens by western blot and immunohistochemistry (IHC). The oncogenic roles of DHX9 in cancers were further verified by in-vitro experiments. We first verified that DHX9 is highly expressed in most tumors but significantly decreased in kidney and thyroid cancers, and it is prominently correlated with the prognosis of patients with different tumors. The phosphorylation level of DHX9 was also increased in cancers. Enrichment analysis revealed that DHX9 was involved in Spliceosome, RNA transport and mRNA surveillance pathway. Furthermore, DHX9 expression exhibited strong correlations with immune cell infiltration, immune checkpoint genes, and tumor mutational burden (TMB)/microsatellite instability (MSI). In liver, lung, breast and renal cancer cells, the knockdown or depletion of DHX9 significantly affected the proliferation, metastasis and EMT process of cancer cells. In summary, this pan-cancer investigation provides a comprehensive understanding of the prognostic and immunological role of DHX9 in human cancers, and experiments indicated that DHX9 was a potential target for cancer treatment.